2017
DOI: 10.5194/hess-21-1651-2017
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity measures in hydrological frequency analysis: review and new developments

Abstract: Abstract. Some regional procedures to estimate hydrological quantiles at ungauged sites, such as the index-flood method, require the delineation of homogeneous regions as a basic step for their application. The homogeneity of these delineated regions is usually tested providing a yes/no decision. However, complementary measures that are able to quantify the degree of heterogeneity of a region are needed to compare regions, evaluate the impact of particular sites, and rank the performance of different delineati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The performance of several pooling group approaches may be assessed in many ways (e.g., Requena, Chebana, & Ouarda, ). In the present study, the assessment of the approaches for quantile estimation is done by a procedure through which both quantile estimation and uncertainty are evaluated to identify an accurate and robust approach.…”
Section: Methodsologymentioning
confidence: 99%
“…The performance of several pooling group approaches may be assessed in many ways (e.g., Requena, Chebana, & Ouarda, ). In the present study, the assessment of the approaches for quantile estimation is done by a procedure through which both quantile estimation and uncertainty are evaluated to identify an accurate and robust approach.…”
Section: Methodsologymentioning
confidence: 99%
“…G ranges from 0 to 1: the former is obtained when all t (i)' s are equal and the latter when all but one value are equal to zero. Requena et al (2017) demonstrated that, in the context of a simulation framework, the G performed as the best heterogeneity measure among the evaluated measures.…”
Section: Heterogeneity Measures For Pooling-groupsmentioning
confidence: 94%
“…1127 Water Resources Research PUBLICATIONS Viglione et al (2007) and Castellarin et al (2008). Recently, Requena et al (2017) tested the performance of different heterogeneity measures in the context of a simulation-based general framework, concluding that the assumption-free Gini index (Ceriani & Verme, 2012;Gini, 1912) applied to the at-site L-variation coefficient (L-CV) over a region provided the best results.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous time and frequency analysis methods are usually adopted to investigate the variations of flood event metrics at station scale, including temporal trend analysis methods (e.g., Mann-Kendall test, segmented regression model) (Shao and Campbell., 2002;Chen and Li, 2011a;Zhang et al, 2011b;Wang et al, 2015), change point tests (e.g., Pettit test, Mann-Kendall test, moving t-test) (Zheng et al, 2007;Li et al, 2008;She et al, 2017), periodicity analysis (e.g., wavelet analysis) (Anctil, 2010;Yang et al, 2018) and frequency analysis (e.g., copula analysis, entropy theory) (Zhang et al, 2011a;Singh, 2015). Most of existing studies mainly focus on flood magnitude metrics (e.g., flood volume, peak flood) and their frequencies at station scale (Milly et al, 2002a;Rogger et al, 2012;Xia et al, 2012;Ma et al, 2014;Requena et al, 2017;Merz et al, 2018;Sun et al, 2018). However, all of these findings are still difficult to reveal comprehensive variation characteristics at basin scale.…”
Section: Introductionmentioning
confidence: 99%